Landscape metrics and environmental quality in the forest remaining of the Ribeirão Quilombo in Campinas/SP - Longo, Regina Márcia; da Silva, Alessandra Leite; Carvalho, Marcela Merides; Ribeiro, Admilson Írio [UNESP] (Universidade Federal de Santa Maria, 2024)
Forest remnants play an important role within urban ecosystems, contributing significantly not only to the environmental quality of municipalities, but also to improving social, economic and aesthetic aspects. In this context, applying and analyzing tools that can contribute to the environmental discussion of these ecosystems become an important contribution in the management of these spaces within the municipalities. The present work aimed to analyze and discuss the forest fragmentation and the environmental quality of the existing forest fragments in the hydrographic basin of the Quilombo River, located in the municipality of Campinas/SP, which is an area that suffers from the processes of urbanization, soil sealing and floods. In general, the procedures performed to assess the environmental quality of forest remnants in the watershed under study were carried out in five main stages: (1) Mapping of forest remnants; (2) Landscape metrics calculations; (3) Environmental Quality Assessment of the remnants; (4) Statistical analysis of data; and, finally, (5) Diagnosis of hydrographic basins based on the results obtained. In general, it can be observed that the Quilombo basin, characterized by the high degree of use and occupation of the soil and predominance of urbanized areas, with non-critical soil and slope conditions, and the forest remnants are predominantly of medium size and have similar conditions of nearest neighbor distance (ENN), where approximately 50% of them are less than 60 m away from their nearest neighbor. Given these conditions, the management and conservation actions of natural vegetation in the Quilombo basin can hardly be based on the connectivity of the remnants. It is indicated that actions are proposed especially aimed at mitigating the edge effects that have acted on these remnants and guaranteeing the effectiveness and quality of the ecological processes involved.
Métricas da paisagem e qualidade ambiental nos remanescentes florestais do Ribeirão Quilombo em Campinas/SP
Keywords: Floods; Forest remnants; Ribeirão Quilombo Basin